The Effect of Social Media Language on EFL Learners’ Academic Writing Performance. Case of Master OneLinguistics Students at M’sila University. - Miss. NedjlaBENSAIDDr.Mourad TOUATI, Miss. Fatima Zohra MOUMEN (My University, 2019)
ABSTRACT The revolution of technology has brought a great change among people. The new digital social media tools carry much weight for education and English language learning. This research aims to investigate to what extent social media may affect students’ academic writing performance. To explore this effect, this research was conducted at the University of Msila. A descriptive method was applied for the current study in which a sample of 25 teachers and 75 students of first-year master linguistic students were selected from the English department. Qualitative and quantitative tools were used during data gathering and analysis. Two questionnaires were addressed for both teachers and students with corpus analysis of some students’ exam papers and some extracts of their daily conversation in Facebook Messenger, Instagram, and WhatsApp. The results indicated that social media and the Netspeak have positive effect outweighing the negative effects on first-year master linguistic students’ language learning and writing. The findings reveal that students prefer online learning that motivates them to improve their language learning and writing. Chat rooms may help students and teachers to exchange experiences and course relate material, and engage students in assignments that enhance their writing. However, the findings confirmed that social media language has a negative influence on some students’ writing. Students use abbreviations and short form of words unconsciously in their formal writing due to their overuse of texting language. Their mistakes in grammar, punctuation, and capitalization are not related only to the overuse of social media but also to their lack of linguistic proficiency. The study proposes taking into account the conventions of writing in the academic environment. In addition, teachers should be innovative and apply social networks in their classrooms in order to achieve better motivation for students and enhance their awareness about the dangers of texting language on their academic writing. Résumé La révolution des technologies a permis un changement significatif dans la vie des gens. De ce fait, les réseaux sociaux contribuent à leurs tours dans l'éducation et l'apprentissage de la langue anglaise. Cette recherche vise à déterminer dans quelle mesure les réseaux sociaux peuvent affecter la performance académique des étudiants à l'écrit. Afin d'explorer cet effet, une recherche a été menée à l'université de M’sila en appliquant une méthode descriptive,un échantillon de 25 enseignants et de 75 étudiants de première année master linguistique ont été sélectionnés du département d’anglais. Des outils qualitatifs et quantitatifs ont été utilisés lors de la collecte et de l'analyse de données. Deux questionnaires ont été adressés aux enseignants et aux étudiants et une analyse despapiersdes épreuves de certains étudiants et des extraits de leurs conversations quotidiennes sur Facebook Messenger, Instagram et WhatsApp. Les résultats ont montré que les réseaux sociaux et le Netspeak ont des effets positifs supérieurs aux effets négatifs sur l’enseignement apprentissage des étudiants de première année master linguistique et que ces étudiants préfèrent un apprentissage en ligne qui les motive à améliorer leur apprentissage et leur performance à l'écrit. Les Chats peuvent aider les étudiants et les enseignants à échanger leurs expériences et leurs contenus, et à engager les étudiants dans des tâches qui les enrichissent à l'écrit. Cependant, les résultats ont confirmé que le langage des réseaux sociaux avait une influence négative sur l’écriture de certains étudiantes. Ils utilisent des abréviations et des formes abrégées de mots de manière inconsciente dans leur écriture académique en raison de leur utilisation excessive de la langue des textos. Leurs erreurs de grammaire, de ponctuation et de capitalisation ne sont pas uniquement liées à l'utilisation abusive des réseaux sociaux, mais également à leur manque de compétences linguistiques. En outre, cette recherche propose de prendre en compte les conventions d'écriture en milieu académique. Ainsi, les enseignants doivent faire preuve d'innovation et utiliser les réseaux sociaux dans leurs classes afin de motiver davantage les étudiants et de les sensibiliser aux dangers du langage textuel dans leurs écrits universitaires.
Keywords: Key terms: academic writing, ICTs, media, social media, social netorking sites, addiction.